2018
DOI: 10.29103/mjml.v1i1.741
|View full text |Cite
|
Sign up to set email alerts
|

The effect of realistic mathematics education on student's mathematical communication ability

Abstract: This study aims to obtain a description of the application of Realistic Mathematic Education (RME) that can improve students' mathematical communication ability. The type of research used is a classroom action research that refers to the design of Kemmis and Mc.Taggart research they are planning, action, observation, and reflection. The results showed that Implementation of mathematics learning with Realistic Mathematics Education (RME) approach that can improve mathematical communication ability is a mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 0 publications
1
29
0
5
Order By: Relevance
“…PBL can optimize students' thinking abilities through group work processes so students can improve, hone, empower, and test their thinking abilities on an ongoing basis. In other words that PBL can facilitate the process of checking out students' answers in completing systematic and structured mathematical communication skills compared to conventional learning (Surya et al, 2018).…”
Section: A Introductionmentioning
confidence: 99%
“…PBL can optimize students' thinking abilities through group work processes so students can improve, hone, empower, and test their thinking abilities on an ongoing basis. In other words that PBL can facilitate the process of checking out students' answers in completing systematic and structured mathematical communication skills compared to conventional learning (Surya et al, 2018).…”
Section: A Introductionmentioning
confidence: 99%
“…Mathematics is an important science to be learned because mathematics is a science that has a unique characteristic as science, which has an abstract object, the pattern on axiomatic and deductive thinking, and based on truth (Afandi, 2018;Mursalin et al, 2018;Fonna, 2018;Amalia et al, 2018). With such unique characteristic, mathematics is useful in developing skill and creating learner personality (Mawaddah, 2015;Flora, 2017;Setiawan, 2006;Trisnawati, 2018 ). Mathematics as base science is also needed to achieve high-quality success.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the results of research conducted by Zakaria and Ihsan (2007) concluded that cooperative learning model provides a better learning outcome than for traditional learning model (conventional). In the implementation of cooperative learning, the model requires the participation and cooperation in the learning group (Trisnawati, 2018). Cooperative learning is a learning model by using the grouping system or a small team of between four to six people who have a background in academic ability, gender, race or ethnicity different (heterogeneous) (Vienna Sanjaya, 2010: 220).…”
Section: Introductionmentioning
confidence: 99%